Dilema Konservatisme: Analisis Dampak Retensi Tradisi Terhadap Stagnasi Inovasi Pesantren Salaf - Ahmad Burhan Jazuli (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This Study Aims To Explore The Phenomenon Of Declining Public Interest In Salaf Islamic Boarding Schools (Pesantren Salaf) And Analyze The Root Causes Of Institutional Innovation Stagnation. Amidst The Waves Of Educational Disruption And Global Pragmatism, Salaf Pesantren Faces An Existential Dilemma Between Maintaining The Originality Of The Classical Texts (Kitab Kuning) And The Demands Of Modernity. Using A Qualitative-Descriptive Method With A Phenomenological Approach, Data Were Collected Through Field Observations, Documentation, And In-Depth Interviews With Boarding School Leaders (Kyai) And Parents. The Results Indicate That The Decline In Enrollment Is Triggered By Three Main Factors: (1) Centralized Charismatic Leadership That Hinders Managerial Professionalism; (2) Resistance To Administrative Formalization Resulting In The Absence Of Formal Diplomas; And (3) Lagging Infrastructure And Digital Literacy (Cultural Lag). This Study Concludes That Rigid Conservatism Has Become A Barrier To The Competitive Advantage Of The Pesantren. As A Solution, "Traditionalist Innovation" And The Optimization Of Muadalah Certification Are Required To Ensure Salaf Pesantren Remains Relevant Without Losing Its Scholarly Identity.